1992
DOI: 10.1083/jcb.117.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 200-kD, brefeldin-sensitive protein on Golgi membranes

Abstract: Abstract. A mAb A717 raised against canine liver

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 47 publications
6
71
0
Order By: Relevance
“…Dissociation of p200 from 2946 Lencer, de Almeida, Moe, Stow, Ausiello, and Madara Golgi membranes occurs rapidly upon exposure to BFA and precedes gross disruption ofGolgi morphology (36). We found that in T84 cells not treated with BFA mAbs against p200 labeled perinuclear structures consistent with the location of Golgi stacks (data not shown).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Dissociation of p200 from 2946 Lencer, de Almeida, Moe, Stow, Ausiello, and Madara Golgi membranes occurs rapidly upon exposure to BFA and precedes gross disruption ofGolgi morphology (36). We found that in T84 cells not treated with BFA mAbs against p200 labeled perinuclear structures consistent with the location of Golgi stacks (data not shown).…”
Section: Resultssupporting
confidence: 59%
“…For immunocytochemical localization of the Golgi associated protein p200 (36), monolayers grown on glass coverslips were incubated in HBSS with and without BFA for 30 min at 370C and fixed as described above. The fixed monolayers were permeabilized by incubation in 1% Triton X-100 in PBS for 20 min at 21'C, and then washed extensively in PBS containing 1% BSA (PBS/BSA).…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise structure of the 4.1B 200 variant has yet to be defined, we feel confident that this Golgi-associated constituent is a protein 4.1B because of the high specificity of our anti-4.1B-HP antibody, as evidenced by: (1) its failure to recognize other members of protein 4.1 family; (2) its failure to recognize any band in 4.1B-knockout tissues; and (3) the reduction of 4.1B 200 protein in siRNA-treated cells with a 4.1B-specific sequence. It is also interesting to note that a monoclonal antibody against canine liver Golgi membrane showed that a 200 kDa, BFA-sensitive protein was associated with the Golgi (Narula et al, 1992), although its identity and function are still uncertain. It has been shown that Na + /K + -ATPase transport from endoplasmic reticulum to Golgi depends on the Golgi spectrinankyrin G119 skeleton (Devarajan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It also is supported by the finding that BFA-resistant Chinese hamster ovary (CHO) lines appear to produce an Arf1-type GEF (Melancon et al, 1997). Therefore, wherever Arf1 and its associated GEF are localized is the initial site of BFA action.BFA-sensitive GEFs are localized to the Golgi apparatus of mammalian cells (Narula et al, 1992;Mansour et al, 1999), as are Arf1p and Arf3p (Stearns et al, 1990;Peters et al, 1995). At least three Arf1p binding sites exist in the mammalian Golgi apparatus: the trans-Golgi network, where Arf1p is involved in the recruitment of the AP-1 adaptor complex of clathrin-coated vesicles (Traub et al, 1993;Boman et al, 2000); and the two compartments where COPI-coated vesicles are formed: the cis-cisternae (Oprins et al, 1993) and the ER-Golgi intermediate compartment (Griffiths et al, 1995;Martinez-Menarguez et al, 1999).…”
mentioning
confidence: 99%